1999
DOI: 10.1111/1467-9507.00098
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Reactivity and Emotional Regulation Strategies as Predictors of Social Behavior with Peers During Toddlerhood

Abstract: Fifty-six mothers and their 24-month-old toddlers were observed on two occasions in a series of laboratory procedures designed to assess relations between emotional functioning (emotional reactivity and emotion regulation) in an individual assessment and social behavior with a same-sex peer. Emotional reactivity was assessed using two frustration tasks designed to elicit distress. Emotional regulation was assessed by examining the child's behaviors (venting, distraction, focal-object focus, self-orientation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
145
2
9

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(166 citation statements)
references
References 32 publications
7
145
2
9
Order By: Relevance
“…Although the developmental literature does not tend to use self-report measures to assess personality, it has been suggested that effortful control is an important precursor to adult levels of trait agreeableness (Ahadi & Rothbart, 1994;Cumberland-Li, Eisenberg, & Reiser, 2004;Kochanska & Knaack, 2003). This suggestion is consistent with data indicating that both effortful control (Calkins, Gill, Johnson, & Smith, 1999) and agreeableness (Martin, Watson, & Wan, 2000) are inversely related to anger and aggression.If effortful control is a substantial precursor of agreeableness, then the developmental literature makes some other points that deserve more systematic attention. First, the construct of effortful control is broader than that of anger-control, encouraging a more extensive conceptualization of agreeableness as self-regulation.…”
supporting
confidence: 56%
“…Although the developmental literature does not tend to use self-report measures to assess personality, it has been suggested that effortful control is an important precursor to adult levels of trait agreeableness (Ahadi & Rothbart, 1994;Cumberland-Li, Eisenberg, & Reiser, 2004;Kochanska & Knaack, 2003). This suggestion is consistent with data indicating that both effortful control (Calkins, Gill, Johnson, & Smith, 1999) and agreeableness (Martin, Watson, & Wan, 2000) are inversely related to anger and aggression.If effortful control is a substantial precursor of agreeableness, then the developmental literature makes some other points that deserve more systematic attention. First, the construct of effortful control is broader than that of anger-control, encouraging a more extensive conceptualization of agreeableness as self-regulation.…”
supporting
confidence: 56%
“…Las estrategias basadas en el cambio de atención como distraerse, auto calmarse y buscar consuelo, dirigen la atención del niño lejos de la fuente del estrés y se asocian con menor malestar emocional (Buss & Goldsmith 1998;Calkins, Gill, Johnson & Smith. 1999;Grolnick, Bridges & Connell, 1996).…”
Section: International Journal Of Psychological Researchunclassified
“…En contraste, cuando las madres utilizaron la estrategia activa de distracción, los niños fueron capaces de redireccionar su atención y disminuir la intensidad de la reacción emocional, hallazgo acorde a los resultados de otros investigadores (Buss & Goldsmith 1998;Calkins, Gill, Johnson & Smith. 1999;Grolnick et al, 1996), quienes señalan que las estrategias de las madres basadas en la distracción, permiten a los niños enfocar su atención lejos de la fuente de estrés contribuyendo a disminuir la intensidad del malestar emocional.…”
Section: Regulación Maternal Y Esfuerzo De Controlunclassified
“…Esta última habilidade pode favorecer o controle de emoções negativas pelas crianças em situações de conflito com pares, evitando interações agressivas. Pesquisas anteriores já haviam demonstrado uma relação negativa entre a utilização de estratégias de regulação de emoções e a freqüência de comportamentos agressivos (Calkins, Gill, Johnson, & Smith, 1999).…”
Section: Inteligência Emocional Aceitação Social E Atributos Comportunclassified